Markov Chain Reliability Model of Cogeneration Power Plant Substation - Valakevičius, E.; Šnipas, M.; Radziukynas, V. (Elektronika ir Elektrotechnika, 2013)
The paper presents a Markov chain reliability model of a cogeneration power plant substation. Stochastic automata networks formalism and functional transition rates were used to specify the reliability behavior of a system. Iterative solution techniques were used to find steady-state solution of Markov models with different sets of randomly generated failure and repair rates. Modeling results were used to perform uncertainty and sensitivity analysis of the reliability model.DOI: http://dx.doi.org/10.5755/j01.eee.19.5.1214